Thoracoabdominal injury with evisceration from a chainsaw assault: a case report - Babatunde Abayomi Salami; Babatunde Adeteru Ayoade; El-Zaki Abdullahi Shomoye; Chigbundu Collins Nwokoro (Journal of Trauma and Injury)
The usual cause of penetrating thoracoabdominal injuries with evisceration are stab wounds with knives and other sharp weapons used during fights and conflicts. Evisceration of the abdominal viscera as a result of trauma, with its attendant morbidity and mortality, requires early intervention. Gunshot wounds can also cause penetrating thoracoabdominal injuries. We report the case of a 52-year-old male patient, a worker at a timber-processing factory, who was assaulted with a chainsaw by his colleague following a disagreement. He was seen at the accident and emergency department of Olabisi Onabanjo University Teaching Hospital, Sagamu, Nigeria with a thoracoabdominal injury about 1.5 hours after the attack. He had a left thoracoabdominal laceration with abdominal evisceration and an open left pneumothorax. He was managed operatively, made a full recovery, and was discharged 16 days after admission. He was readmitted 4 months after the initial surgery with acute intestinal obstruction secondary to adhesions. He underwent exploratory laparotomy and adhesiolysis. He made an uneventful recovery and was discharged on the 9th postoperative day for subsequent follow-up.